The application of P–T–X(CO2) modelling in constraining metamorphism and hydrothermal alteration at the Damang gold deposit, Ghana. (10th September 2013) - White, A. J. R.; Waters, D. J.; Robb, L. J.
Abstract: Orogenic gold mineralization at the Damang deposit, Ghana, is associated with hydrothermal alteration haloes around gold‐bearing quartz veins, produced by the infiltration of a H2 O–CO2 –K2 O–H2 S fluid following regional metamorphism. Alteration assemblages are controlled by the protoliths with sedimentary rocks developing a typical assemblage of muscovite, ankerite and pyrite, while intrusive dolerite bodies contain biotite, ankerite and pyrrhotite, accompanied by the destruction of hornblende. Mineral equilibria modelling was undertaken with the computer programthermocalc, in subsets of the model system MnO–Na2 O–CaO–K2 O–FeO–MgO–Al2 O3 –SiO2 –CO2 –H2 O–TiO2 –Fe2 O3, to constrain conditions of regional metamorphism and the subsequent gold mineralization event. Metapelites with well‐developed amphibolite facies assemblages reliably constrain peak regional metamorphism at ~595 °C and 5.5 kbar. Observed hydrothermal alteration assemblages associated with gold mineralization in a wide compositional range of lithologies are typically calculated to be stable within P–T–X (CO2 ) arrays that trend towards lower temperatures and pressures with increasing equilibrium fluid X (CO2 ). These independent P–T–X (CO2 ) arrays converge and the region of overlap at ~375–425 °C and 1–2 kbar is taken to represent the conditions of alteration approaching equilibrium with a common infiltrating fluid with an X (CO2 ) of ~0.7. Fluid‐rock interaction calculations with M–X (CO2 ) diagrams indicate that the observed alteration assemblages are consistent with the addition of a single fluid phase requiring minimum fluid/rock ratios on the order of 1.